Complete Metabolic Response by 18F-FDG PET/CT to Atezolizumab Plus Bevacizumab in Patients With Advanced Hepatocellular Carcinoma. (20th May 2023) - Uchida, Yoichiro; Yoh, Tomoaki; Fukui, Ayaka; Takai, Atsushi; Hatano, Etsuro
Abstract: Nowadays, atezolizumab plus bevacizumab is recommended for advanced hepatocellular carcinoma (HCC) as the first-line systemic chemotherapy. Nevertheless, the data with regard to the tumor response still remain limited. We report a complete metabolic response assessed by 18 F-FDG PET/CT in a 74-year-old man with advanced HCC who underwent atezolizumab plus bevacizumab followed by radical hepatectomy. Furthermore, pathological examination revealed that the tumor showed complete response for this therapy. This case suggests that 18 F-FDG PET/CT represents clinical relevance as a useful approach for therapeutic assessment of immune-oncology drugs in HCC.